Relationships of Service Response with Service Quality in Emergency Department of Rsud Dr. Loekmono Hadi, Kudus, Indonesia - Nur Hidayat1 , Ahsan1 , Masruroh Rahayu1 , Abdul Rohim Tualeka2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Emergency Department is a service installation in a hospital that provides the first service for 24 hours topatients with the threat of death and disability in an integrated manner by involving various multidisciplinarysciences and multi professions including nursing services. The quality of service in IGD can be assessedbased on 2 (two) things, namely service quality and minimum service standards (SPM). The main factor inevaluating service quality in the emergency room is the speed of service response time or response time.The purpose of service response time is the delivery of services that are fast, responsive and able to saveemergency patients who need help. This research was conducted in January 2020 in the Emergency Roomat Dr. Loekmono Hadi Kudus. It aims to analyze the relationship between service response time and servicequality in the ED. This is a descriptive quantitative study carried out through analytic observation with across sectional approach. The population in this study was the visit of all patients who entered and receivedservices by the guardian in the emergency room as much as 25-35 patients per shift per day, while thenumber of samples in this study were 117 patients. The independent variable in this study is service responsetime and the dependent variable is service quality. Data were analyzed by bivariate test using Kendall Tau.The p-value is 0.963, thus, there was no relationship between service response time and service quality in theEmergency Room Dr. Loekmono Hadi Kudus. Further research is needed because the limited understandingand knowledge of the sample influences the evaluation of service response time to service quality becomesirrelevant.